PROSEDUR PENGADAAN BARANG DAN JASA DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU DAERAH PROVINSI SULAWESI UTARA - Sarapi, Lidya Angrini; Saerang, David P.E.; Afandi, Dhullo (Universitas Sam Ratulangi, 2020)
Procurement of goods and services that are not healthy has an impact on the losses to be borne by the community, including the low quality of services received from the government. This study aims to analyze and test the suitability of the procedures for the procurement of goods and services in the Investment and One Stop Integrated Service of North Sulawesi with Presidential Regulation Number 16 of 2018 concerning Procurement of Government Goods / Services and Government Regulation Number 60 of 2008 Government Internal Control System (GICS). The analytical method used in this study is a descriptive method that starts with collecting data to be analyzed then a conclusion is drawn and the type of research used is descriptive qualitative. The results of the study obtained that the Procedure for Procurement of Goods and Services in the Investment and One Stop Integrated Service of North Sulawesi adjusted to Government Regulation Number 16 of 2018 and Government Regulation Number 60 of 2008 has been carried out well.